2014
DOI: 10.1002/ange.201401004
|View full text |Cite
|
Sign up to set email alerts
|

Aza[6]helicene Platinum Complexes: Chirality Control of cis–trans Isomerism

Abstract: It was serendipitously observed that cis‐[PtCl2(NCEt)PPh3] reacted differently with either racemic or enantiopure 4‐aza[6]helicene, giving respectively cis (racemic) and trans (enantiopure) [PtIICl2(4‐aza[6]helicene)PPh3] complexes. This unexpected reactivity is explained through a dynamic process (crystallization‐induced diastereoselective transformation) and enables a new aspect of reactivity in chiral transition‐metal complexes to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…found twice as high as for 4-aza [6] 99 in agreement with the presence of two azahelicene moieties. Note that a similar strategy was applied by Srebro-Hooper, Crassous, et al to the preparation of helicene-bipy 51 (Scheme 13 and Table 6).…”
Section: Basesupporting
confidence: 67%
See 2 more Smart Citations
“…found twice as high as for 4-aza [6] 99 in agreement with the presence of two azahelicene moieties. Note that a similar strategy was applied by Srebro-Hooper, Crassous, et al to the preparation of helicene-bipy 51 (Scheme 13 and Table 6).…”
Section: Basesupporting
confidence: 67%
“…Later on in 2014, the coordination of 4-aza [6]helicene 41a 4 to square planar platinum(II) revealed a new aspect of reactivity in chiral transition metal complexes. 99 Indeed, our group has observed that cis-[PtCl 2 (NCEt)PPh 3 ] (cis-109) reacted differently with either racemic or enantiopure 4-aza [6]helicene 41a 4 giving respectively cis (racemic, 110) and trans (enantiopure, 110') [PtCl 2 (41a 4 )PPh 3 ] complexes (Scheme 27). This unexpected reactivity is explained through a dynamic process (crystallization-induced diastereoselective transformation).…”
Section: Coordination Chemistry Of Pyridohelicenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with racemic pyrido[ n ]helicenes ( n =5,6,7) and their derivatives, both enantio‐ and diastereomerically pure pyrido[ n ]helicene‐like molecules ( n =5,6) were prepared by employing the chiral substrate‐controlled cyclisation of the corresponding enantiopure cyanodiynes. It establishes a new methodology for the preparation of attractive pyridohelicenes and their analogues,, which have already been studied theoretically as well as experimentally in the context of basicity,, coordination chemistry, organocatalysis, chiroptical properties, dynamic behaviour, thermopower, or photonics …”
Section: Discussionmentioning
confidence: 99%
“…The understanding and use of this effect is one of the pillars for the improvement of synthetic and predictive capabilities of inorganic chemists. Particularly, the trans influence, can be studied in different ways . If the atom of the ligand interacting directly with the metal center is an NMR active species, this technique becomes a powerful tool to get insights into this phenomenon .…”
Section: Introductionmentioning
confidence: 99%